Risk of Leukemia and Brain Tumors in Children Exposed to Pesticide Residual in Households and Approaches to Reduce its Side Effect - Ismaeil Alizadeh; Mohammad Amin Gorouhi; Abbas Aghaei Afshar; Maryam Faraji; Mojtaba Nakhaeipour; Fatemeh Pourchangiz (Mazandaran University of Medical Sciences, 2021)
Context: Using various pesticides to control pests and vectors of diseases has a long history in households worldwide. However, most pesticides are considered toxic to and harmful to the environment.  Evidence Acquisition: Electronic databases such as Google Scholar, PubMed, and Scopus were searched using the following search terms: "children", "pesticide residues", "risks", "leukemia", and "brain neoplasms". This review was designed to identify the relevant electronic studies published from January 2000 to February 2020. Results: Children are more susceptible to pesticides because of their underdeveloped metabolic processes and disability to detoxify chemicals. Over 30% of the children's diseases are due to environmental factors, including pesticides. The possibility of children's pesticide exposure inside of urban houses is more than outside. In general, children can be exposed to pesticides in two ways: Direct and indirect contact. Direct contact refers to hand-to-mouth behavior in daily plays that absorbs household pesticides. Indirect contact refers to exposure via their parents' work in hazardous environments and during pregnancy. There is a significant association between pesticide exposure via households and some cancers in children, such as leukemia and brain tumors. Conclusions: Due to the positive association between pesticide residues in households and the risk of cancers in children, public health policies must be adopted to minimize children's exposure to pesticides in the urban household.